Análisis sobre los procesos de producción y comercialización de la papa (Solanum tuberosum), variedad súper chola en el Cantón Tulcán, Provincia del Carchi - Meneses Fueltala, Washington Vicente (2019)
SUMMARY According to the problem of the cultivation of the potato variety super chola in the Tulcán canton of the province of Carchi, should be studied mainly the intermediation from the producer to the final customer resulting in the constant fluctuation of prices, the increase in the price of the product and as a consequence the speculation of prices in small spaces of time, accompanied by a non-existent planning in the sowing, which often causes a bonanza of product, scarcity and even loss of crops even when sowing.The potato is one of the main crops of the Ecuadorian highlands, it is produced in ten provinces mainly in Carchi, Pichincha, Tungurahua, Chimborazo and Cotopaxi, in whose markets the Super Chola, Gabriela, Esperanza, Roja, Fripapa and Mary.In Cantón Tulcán the main varieties of potatoes that are sown are the Super Chola and Capiro, the areas that are dedicated to the production of this crop are Julio Andrade, El Carrizal, El Capote, Tetes, Tufiño. Especially in the parish of Julio Andrade, the trade of this tuber is the main income in the families that daily transport the product. On the other hand, the potato trade is maintained thanks to the associativity maintained by the farmers who daily take the product to the local markets of the Canton. With the marketing strategies it is intended to help to boost the sector, what is sought is the profitability directed towards the farmer and his cultivation, this is only achieved with innovation and product diversification. Keywords: Potato super chola, production, marketing margins, strategies.